Systemic immune-inflammation index (SII) is useful to predict survival outcomes in patients with surgically resected esophageal squamous cell carcinoma - Gao, Yibo (J Cancer, 2019)
Background: The systemic immune-inflammation index (SII) has been reported to be associated with patient survival in various kinds of solid tumors. However, just few studies have focused on its prognostic value in patients with surgically resected esophageal squamous cell carcinoma (ESCC). Materials and Methods: This study was a single-institution, retrospective analysis of 468 ESCC patients who underwent curative esophagectomy at the Department of Thoracic Surgery, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College between 2005 and 2008. The receiver operating curve (ROC) was plotted to compare the discrimination ability of the SII and other inflammatory factors for overall survival (OS) and disease-free survival (DFS). Univariate and multivariate analyses were performed based on the Cox proportional hazards regression model. Results: The SII, neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) were all associated with OS in ESCC patients. The SII, NLR, and PLR were independent prognostic factors for OS (hazard ratio (HR) = 1.604, 95% confidence interval (CI) 1.247-2.063, P < 0.001; HR = 1.396, 95% CI 1.074-1.815, P = 0.013; HR = 1.370, 95% CI 1.067-1.758, P = 0.013, respectively) and DFS (HR = 1.681, 95% CI 1.307-2.162, P < 0.001; HR = 1.376, 95% CI 1.059-1.788, P = 0.017; HR = 1.398, 95% CI 1.089-1.794, P = 0.009, respectively). The area under the curve (AUC) for SII was bigger than NLR, PLR, and MLR (0.553, 0.540, 0.532, and 0.521, respectively). Conclusion: The SII is a simple and promising prognostic predictor for patients with surgically resected ESCC. The prognostic value of SII is superior to those of the NLR, PLR and MLR. Moreover, the SII retained prognostic significance in stage I-II ESCC subgroup (OS, DFS) and stage III ESCC subgroup (DFS).